Visuomotor Reaction Time Performance in Collegiate Contact and Limited Contact Team Sports - Mike Swoboda; Ashley Bloodgood; Johanna Jessop; Nardia Padilla (Journal of Interdisciplinary Sciences)
This study assessed baseline reaction time (RT) performance of collegiate student-athletes participating in a contact team sport. The goal was to determine if significant differences in visuomotor RT existed between athletes who had previously sustained a concussion and were now cleared to play their respective sport against a control population of peers who have not sustained a concussion. This study employed a cross-sectional, quantitative, correlational study design. 269 Athletes from contact team sports were identified for potential inclusion. 62 enrolled in the study and 60 participants completed the study. Participants completed three tests to assess their reaction time: Trail Making Test, Ruler Drop Test, and Light Sensor Reaction Test. Participants completed intake paperwork indicating if they had a previous concussion. Participants were 70% female (n=42) and 30% male (n=18). Over 38% of participants (n=23) indicated a prior history of at least one diagnosed concussion or TBI. Mean age was 20.7 ± 1.5 years. No significant differences were found between groups (p>0.05). Collegiate athletes who recovered from a concussion do not demonstrate delays in RT compared to their non-concussed peers. Contact sport athletes should be allowed to return to play their respective sports when they have met their established healing goals via objective performance evaluation and subjective emotional readiness to play.